Electronic Alberta Stroke Program Early CT score change and functional outcome in a drip-and-ship stroke service - Purrucker, Jan; Mattern, Nicole; Herweh, Christian; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; Nagel, Simon; Gumbinger, Christoph (Journal of neuroInterventional surgery, 2020)
Background Debate continues as to whether patients with acute ischemic stroke with (suspected) large vessel occlusion benefit from direct referral versus secondary transportation. Aims To analyze the change in early infarct signs, collaterals, and acute ischemia volume and their association with transfer time and functional outcome. Methods We retrospectively analyzed consecutive transfers between 2013 and 2016 for patients with anterior circulation stroke transported from referring hospitals to our center as potential candidates for thrombectomy. Alberta Stroke Programme Early CT Scores (ASPECTS) were automatically calculated on external and in-house CT using the Brainomix e-AS PECTS software, and collaterals were assessed using the e-C TA tool. Functional status after stroke using the modified Rankin scale (mRS) was obtained. Results 102 patients with CT scans both at the referring hospital and our center were identified. During patient transfer, e-AS PECTS declined by a median of 1 point (0-2). Functional outcome correlated with the change in e-AS PECTS (decline, n=54) (Spearman r s=0.322, 95%CI 0.131 to 0.482, p=0.001). The median image-to-image time was 149 min (IQR 113-190), but did not correlate with change in e-AS PECTS (p=0.754) and mRS score at 3 months (p=0.25). Preserved good collateral status assessed at the comprehensive stroke center was associated with better functional outcome (r s=-0.271, 95%CI -0.485 to -0.037, p=0.02). Conclusions Patient transfer in a drip-and-ship network was associated with declines in e-AS PECTS associated with worse functional outcome. Image-to-image time did not influence this association, but worsening collateral status did.